STRATEGY OF ENVIRONMENTAL LEGAL ARRANGEMENT AS AN EFFORT TO PREVENT NATURAL DISASTERS, FLOODS, AND LANDSLIDES IN NORTH SULAWESI - Flora Pricilla Kalalo; Nelly Pinangkaan; Reymen M. Rewah (Transpublika Publisher, 2024)
The prevention of violations of Environmental Law is based on Law Number 32 of 2009, which requires all members of society to comply with the law. National guidelines for preventing natural disasters have been established by BNPB, Provincial and Regional Governments as policies for society to follow. Compliance with environmental laws is crucial to ensure that people do not live in prohibited areas designated by the government. Failure to comply with environmental permits has resulted in losses and casualties during floods and landslides in Manado and North Sulawesi. Environmental standards are regulated by laws and institutions such as BNPB, as well as local government regulations. However, despite these regulations, environmental problems still persist. This research aims to address the legal strategies for structuring environmental law that must be followed by the community, as well as the enforcement strategies and sanctions for those who violate environmental laws. The research uses normative research methods focusing on two indicators: the basic strategies for structuring environmental laws and the enforcement strategies and sanctions for violators.